2014
DOI: 10.1128/jvi.03676-13
|View full text |Cite
|
Sign up to set email alerts
|

Measles Vaccination of Nonhuman Primates Provides Partial Protection against Infection with Canine Distemper Virus

Abstract: Measles virus (MV) is being considered for global eradication, which would likely reduce compliance with MV vaccination. As a result, children will grow up without MV-specific immunity, creating a potential niche for closely related animal morbilliviruses such as canine distemper virus (CDV). Natural CDV infection causing clinical signs has never been reported in humans, but recent outbreaks in captive macaques have shown that CDV can cause disease in primates. We studied the virulence and tropism of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 53 publications
3
63
1
Order By: Relevance
“…3 and 5). These findings are similar to the results of experimental infections in ferrets, seals and Cynomolgus macaques with either CDV or MV, in which a higher tropism was demonstrated for lymphatic tissues von Messling et al, 2004;de Swart et al, 2007;de Vries et al, 2014). In a previous study, SLAM is markedly up-regulated in lymphoid cells of infected tissues after CDV infection, indicating a possible virus strategy to increase amplification in the host (Wenzlow et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3 and 5). These findings are similar to the results of experimental infections in ferrets, seals and Cynomolgus macaques with either CDV or MV, in which a higher tropism was demonstrated for lymphatic tissues von Messling et al, 2004;de Swart et al, 2007;de Vries et al, 2014). In a previous study, SLAM is markedly up-regulated in lymphoid cells of infected tissues after CDV infection, indicating a possible virus strategy to increase amplification in the host (Wenzlow et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Previous field epidemiology and observational studies in China suggested that CDV infection was more common and more relevant clinically in raccoon dogs and foxes than in minks (Zhao et al, 2010a;Wang et al, 2009). Accordingly, it is possible to assume that raccoon dogs or foxes are more susceptible than minks to CDV, although virus-related factors should be also considered when assessing CDV pathogenesis (Nielsen et al, 2009;Jensen et al, 2015;de Vries et al, 2014). For this reason, the differences in susceptibility between these species required thorough investigation using experimental infections.…”
Section: Introductionmentioning
confidence: 97%
“…The rationale for insertion after the P gene was that the N and P proteins are predicted to be required in large amounts, while this location can retain balanced levels of envelope associated M, F, and H proteins. Insertion after the H gene has been successful in previous morbillivirus studies (26,29,30). We designed the constructs so that the ATUs were identical in rMV EZ EGFP(3) and rMV EZ EGFP(6).…”
Section: Discussionmentioning
confidence: 99%
“…The overattenuation of rMV EZ EGFP(6) was a surprise, given that equivalent viruses are apparently unperturbed in other systems (26,29,30). Also, in a previous study where IFN-␣/␤ receptor knockout mice expressing human CD46 were injected intraperitoneally with 5 ϫ 10 6 TCID 50 of Schwarz-based rMVs containing an ATU, the position 3 and 6 viruses induced equivalent immune responses at 28 d.p.i.…”
Section: Fig 3 Target Cells Of Rmv Ez Egfp(3) Egfp Distribution In Mmentioning
confidence: 99%
“…When two independently developed PPRV vaccine strains (Nigeria/75 and Sungri/96) along with a virulent strain of PPRV were used to inoculate cattle, a cross protection against virulent RPV was observed only when virulent PPRV was inoculated in cattle (Holzer et al, 2016a), a finding which is in accordance with very early studies where crude material from animals suffering from PPR was shown to protect cattle from rinderpest (Mornet et al, 1956a). Increased disease outbreaks due to CDV in primates (de Vries et al, 2014) suggests that the presence of measles virus in human population would have prevented disease caused by CDV.…”
Section: Cross Protection Among Morbillivirusesmentioning
confidence: 99%